A review of biosimilars in psoriasis: impacts on efficacy, safety, access, and a first-hand look at biosimilar cost savings within the department of veterans affairs - Rebecca Reese; Shiva Ram Nanavath; Jennifer Martin; Jeffrey B. Travers; Craig A. Rohan (Journal of Dermatological Treatment)
Background Psoriasis is a chronic immune-mediated systemic disease whose treatment has been revolutionized due to the induction of monoclonal antibody-based biologics. However, access to these drugs has been limited due to their high cost. Biosimilars utilize reverse engineering to create a highly similar product to an originator drug following patent expiration and provide an avenue to reduce costs of biologic treatment. This review seeks to synthesize current knowledge about the development, efficacy, and established benefits of biosimilars, including cost savings and increased access to biologic medicines.Results In 2023, the Veterans Health Administration (VA) generated a cost avoidance of over 67 million dollars through use of 6 currently adopted biosimilars across all indications. There is an opportunity for further cost avoidance, with the pre-set percent discount of statutory contract prices necessary for the adoption of future biosimilars, including adalimumab and etanercept, set at over 50%.Conclusions Biosimilars appear to offer an overall effective, safe, and well-tolerated treatment method for patients with psoriasis and are already providing substantial cost savings within the VA. Additional education is needed to address sources of ambivalence for both patients and providers to assist in further uptake of biosimilars for the treatment of psoriasis.